2019
DOI: 10.14309/crj.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Fecalith Presenting as a Submucosal Cecal Mass

Abstract: A wide variety of benign and malignant submucosal lesions may arise from the wall of the large intestine. They can originate in the submucosa or in the muscular propia; furthermore, they can be caused by compression of extrinsic structures.1,2 We report a case of a submucosal mass identified as a fecalith protruding into the cecum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Alhalabi et al suggested that fecalith(s) could be trapped in the appendiceal orifice and develop in the submucosal layer over time [ 12 ]. Bustamante et al suggested that the result of long-term incarceration of an appendicular fecalith or the constant accumulation of feces through fissure(s) in the mucosa cause submucosal fecalith [ 15 , 18 ]. Ito et al favored the hypothesis that intussusception of the appendix, which excludes foreign bodies from the lumen of the appendix, may lead to submucosal fecalith.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alhalabi et al suggested that fecalith(s) could be trapped in the appendiceal orifice and develop in the submucosal layer over time [ 12 ]. Bustamante et al suggested that the result of long-term incarceration of an appendicular fecalith or the constant accumulation of feces through fissure(s) in the mucosa cause submucosal fecalith [ 15 , 18 ]. Ito et al favored the hypothesis that intussusception of the appendix, which excludes foreign bodies from the lumen of the appendix, may lead to submucosal fecalith.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kangaspunta et al demonstrated that preoperative abdominal CT was poor in detecting tumors in patients with acute appendicitis [20]. Since 1981, several studies have described submucosal fecalith(s) mimicking submucosal tumors, as shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18]. Some characteristics of the 12 patients with submucosal fecalith included in our brief literature review included a mean age of 47 years (range, 6-74 years), a female-to-male prevalence ratio of 1:2, and the fecalith was located around the cecum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] They are usually misidentified initially as a submucosal cecal or appendiceal tumor on the abdominal computed tomography scan or during colonoscopy and diagnosed as a fecalith postoperatively after resection due to concern for possible malignancy. 1,2,10 Appendiceal fecaliths are associated with acute appendicitis, intussusception of the appendix, or chronic right lower quadrant abdominal pain. Few reports have been made of asymptomatic patients diagnosed with appendiceal fecaliths during colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Other reports have described appendiceal fecaliths discovered after surgical or endoscopic resections in symptomatic patients. [7][8][9][10][11] They are usually misidentified initially as a submucosal cecal or appendiceal tumor on the abdominal computed tomography scan or during colonoscopy and diagnosed as a fecalith postoperatively after resection due to concern for possible malignancy. 1,2,10 Appendiceal fecaliths are associated with acute appendicitis, intussusception of the appendix, or chronic right lower quadrant abdominal pain.…”
Section: Introductionmentioning
confidence: 99%